Could Faecalibacterium prausnitzii Amount in the Gut Microbiota Be Used to Monitor the COVID-19 Severity? - Demirci, Mehmet (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Demirci M. Could Faecalibacterium prausnitzii amount in the gut microbiota be used to monitor the COVID-19 severity? Turk J Gastroenterol. 2022;33(10):899-900.